Two novel alleles at HLA‐B locus identified in two volunteer bone marrow donors by sequence‐based typing. (3rd November 2012) - Frison, S.; Longhi, E.; Mantovani, M.; Malagoli, A.; De, A.; Piccolo, G.; Poli, F.
Summary Two novel human leucocyte antigen (HLA) class I alleles have been identified in two Italian individuals. HLA‐B*27:07:02 is identical to HLA‐B*27:07:01 except for a nucleotide substitution at position 846 (A‐>G) resulting in a silent mutation. HLA‐B*35:206 differs from the most similar allele, HLA‐B*35:08:01, because of a single base mutation at position 149 (G‐>C) causing an aminoacidic change at codon 26 from Gly to Ala.